Physicochemical Parameters and Bioaccessibility of Lactic Acid Bacteria Fermented Chayote Leaf (Sechium edule) and Pineapple (Ananas comosus) Smoothies - Managa, Millicent G.; Akinola, Stephen A.; Remize, Fabienne; Garcia, Cyrielle; Sivakumar, Dharini (Frontiers in Nutrition, 2021)
In this study, popularly consumed traditional chayote leaves and locally produced pineapple fruit were used to develop a fermented smoothie using lactic acid bacteria (LAB) strains: Lactobacillus plantarum (L75), Weissella cibaria (W64), and their combination (LW64 + 75). The physicochemical parameters [pH, total soluble solids (TSS), and color], total phenols, and carotenoid contents of the smoothies fermented for 48 h and stored for 7 days at 4°C were compared with the unfermented (control) smoothies. Results indicated that LAB fermentation reduced the pH from 3.56 to 2.50 after 48 h (day 2) compared with the non-fermented smoothie at day 2 (pH 3.37). LAB strain L75 significantly reduced the TSS content of the smoothies to 13.06°Bx after 2 days of fermentation. Smoothies fermented by L75 showed overall acceptability after 7 days of storage compared with the non-fermented puree on day 0. The LW64 + 75 significantly reduced the color change (ΔE), which was similar to the control. L75 increased the phenolic content, and W64 enhanced the total carotenoid content of the smoothies after 2 days of fermentation compared with other treatments. The use of an in vitro model simulating gastrointestinal (GI) digestion showed that fermentation with L75 improved the total phenol recovery by 65.96% during the intestinal phase compared with the control. The dialysis phase mimicked an epithelial barrier, and 53.58% of the recovered free soluble are bioavailable from the L75 fermented smoothies compared with the control. The antioxidant capacity of dialyzable fraction of the L75 fermented smoothie was significantly higher than that of the control and smoothies fermented with W64 or LW64 + 75.